RELATIONSHIP BETWEEN SLEEP PATTERNS AND EMOTIONAL INTELLIGENCE OF TEENAGERS IN HEAL VOCATIONAL SCHOOL NAFSIAH STABAT 2020 - Nurhikmah Panjaitan; Yusra Yusra (Institute of Computer Science (IOCS), 2020)
Sleep is one of the physiological needs for humans, which is helpful for the body's recovery process, affecting students' emotional intelligence. Individuals who have good emotional intelligence will be able and easy to relate to other people because they can empathize, motivate themselves, and manage the emotions of others. This study aimed to determine the relationship between sleep patterns and the emotional intelligence of adolescents at SMK Nafsiah. This research method uses a descriptive correlation method with a cross-sectional approach. Data collection was carried out by distributing questionnaires. The sample in this study amounted to 33 respondents. The sampling technique used is random sampling—data analysis using the chy square test. The results showed 12 respondents (26.67%) with good sleep patterns, 24 respondents (53.33%) with good sleep patterns, and 9 respondents (20%) with poor sleep patterns. Based on emotional intelligence, 34 respondents (75.55%) had good emotional development, and 11 respondents (24.45%) had poor emotional development. This research concludes that there is a relationship between sleep patterns and emotional intelligence of SMK Kesehatan Nafsiah Stabat students, with a p-value of 0.000 at df = 2, where sig <α (0.000 <0.05). It is hoped that Nafsiah Health Vocational School students will realize that sleep is a basic/physiological human need. If it is adequately fulfilled, it will have good emotional intelligence